2023
DOI: 10.1002/admi.202202276
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Diverse Oxygen Transport Pathways Across Sr‐Doped Lanthanum Ferrite and Metal‐Perovskite Heterostructures

Abstract: Perovskite structured transition metal oxides are important technological materials for catalysis and solid oxide fuel cell applications. Their functionality often depends on oxygen diffusivity and mobility through complex oxide heterostructures, which can be significantly impacted by structural and chemical modifications, such as doping. Further, when utilized within electrochemical cells, interfacial reactions with other components (e.g., Ni‐ and Cr‐based alloy electrodes and interconnects) can influence the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…By exposing the needle-shaped specimen to 18 O at elevated temperature in situ in a reaction chamber connected via UHV transfer to the APT analysis chamber, diverse oxygen transport pathways across the system can be measured by isotopically resolved APT without air exposure that might further redistribute the anion tracers (Figure 6). 14 We found that a substantial fraction of the O in the (La,Sr)FeO 3 film, ∼84%, was exchanged for 18 O during the anneal (400 °C, 4 h, 3 mbar 99% enriched 18 O 2 ). This rapid oxygen exchange was attributed to an anion-vacancy-mediated diffusion mechanism and facilitated by the large surface area of the film in the needle geometry.…”
Section: In Situ Apt Analysis After Postprocessingmentioning
confidence: 72%
“…By exposing the needle-shaped specimen to 18 O at elevated temperature in situ in a reaction chamber connected via UHV transfer to the APT analysis chamber, diverse oxygen transport pathways across the system can be measured by isotopically resolved APT without air exposure that might further redistribute the anion tracers (Figure 6). 14 We found that a substantial fraction of the O in the (La,Sr)FeO 3 film, ∼84%, was exchanged for 18 O during the anneal (400 °C, 4 h, 3 mbar 99% enriched 18 O 2 ). This rapid oxygen exchange was attributed to an anion-vacancy-mediated diffusion mechanism and facilitated by the large surface area of the film in the needle geometry.…”
Section: In Situ Apt Analysis After Postprocessingmentioning
confidence: 72%